Cultural Integration in Islamic Financial Innovation: Implementation of Istishlahi Principles in Musyarakah Mutanaqishah Contracts in Multicultural Indonesia - Nugroho, Bimo; Ma’rufi, Anwar; Fathudin, Fathudin; Jankauskienė, Dainora; Lousada, Sérgio António Neves (Kawanua International Journal of Multicultural Studies, 2024)
This research analyzes the implementation of the istishlahi (public benefit) principle in the DSN-MUI fatwa concerning Musyarakah Mutanaqishah (Diminishing Partnership) and its application within Indonesia's multicultural context. Employing a qualitative approach with content analysis and systematic literature review, this study examines primary sources, including DSN-MUI Fatwa No.73/DSN-MUI/XI/2008, and secondary sources from academic literature spanning 2015-2024. The findings demonstrate that the implementation of the istishlahi principle in the DSN-MUI fatwa successfully integrates nine fundamental principles (al-’adl, al-maslahah, al-yusr, al-barakah, al-yaqin, al-muwazah, al-istiqraar, al-taysir, and al-amanah) within an adaptive regulatory framework. Comparative analysis of implementation across various regions in Indonesia reveals significant variations in success rates and challenges encountered, with key factors including structural and operational adaptations according to local contexts. Case studies in Aceh, East Java, Makassar, and Sorong highlight the importance of integration with local value systems and active community involvement in successful implementation. This research provides theoretical contributions in developing a new understanding of the istishlahi principle's function as a bridge between Shariah compliance and the practical needs of a multicultural society, as well as practical implications for developing more inclusive and adaptive Islamic financial products.